The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1590/1807-1929/agriambi.v20n7p666-671
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of roasted and ground coffee during storage. Part 2: Bulk density and intergranular porosity

Abstract: A B S T R A C TThe determination of physical properties is an important factor in the design of machinery and the scaling of post-harvest operations. The present study evaluates the influence of the level of roasting and the size of grinding on the physical properties of coffee during storage. The following physical properties were evaluated: true and bulk density, and intergranular porosity. Raw coffee beans (Coffea canephora and Coffea arabica), hulled and dried, were roasted to two different levels: medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Informações a respeito dos caracteres físicos do material ainda podem auxiliar em estudos de transferência de calor e massa e movimentação de ar na massa granular durante processos de secagem ou aeração (GONELI et al, 2011;LI et al, 2019). Atributos físicos, como a massa específica e a porosidade intergranular, também podem ajudar na identificação de perdas quantitativas e qualitativas do produto durante o armazenamento (CORRÊA et al, 2016).…”
Section: Introductionunclassified
“…Informações a respeito dos caracteres físicos do material ainda podem auxiliar em estudos de transferência de calor e massa e movimentação de ar na massa granular durante processos de secagem ou aeração (GONELI et al, 2011;LI et al, 2019). Atributos físicos, como a massa específica e a porosidade intergranular, também podem ajudar na identificação de perdas quantitativas e qualitativas do produto durante o armazenamento (CORRÊA et al, 2016).…”
Section: Introductionunclassified
“…As compared to that of roasted ground coffee, storage of whole roasted coffee beans is preferable for conserving coffee constituents, moisture, and quality, without agglomeration and compactness, probably due to intact cells working as a physical barrier (Toledo et al., ). In ground roast coffee, light‐ to medium‐roasted coffees with high ρ u and ρ ap usually show less agglomeration and compactness (Correa et al., ). These results are based on 2 facts; one is that more finely ground coffee is more tightly agglomerated for a given volume, resulting in a higher weight per volume and lower ρ u .…”
Section: Storagementioning
confidence: 99%
“…The moisture content of ground coffee increases with storage time, and Correa et al. (, ) found that the moisture level can reach up to 3% to 4% (d.b.) from 1% to 2% (d.b.)…”
Section: Primary Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore essential that its storage promotes the reduction of losses for as long as possible. Some authors reported that the storage time of roasted coffee affected the physical properties (CORRÊA et al, 2016a), water content and resting angle of the coffee (CORRÊA et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%